Review of Audit Quality Indicators - Aviany Santi; Dicky Dicky; Windy Dwiyanti (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
Audit quality is the accuracy of the information reported by the auditor by the audit standards used by the auditor of the company's financial statements. This study aims to identify audit quality in several cases that occurred in Indonesia by using audit quality indicators in the form of ethics, people, process, output, and interaction. The research method uses a qualitative descriptive method with the object of analysis in the form of audit quality indicators. The results of this study indicate that the audit ethics quality indicators have the most influence on several cases that occurred in Indonesia.